The Relationship Between Intelligence and Sensory – Motor Perception In Deaf And Dumb Students Aged 13 years Old - Hassan, Bedri; Abdul rahman, Kamran; Mohameed, Zayluan (Journal of Physical Education, 2016)
The aim of the research is to identify the relationship between intelligence andsensory – motor perception in deaf and dumb students aged 13 years old. The researchersused the descriptive method. The subjects were (11) student. Two tests were used to measuresensory – motor perception (Time sensory – motor perception) and (Jumping distancesensory – motor perception). Intelligence was measured using Raven Intelligence scale. Thedata was collected and treated using proper statistical methods. The results showed greatcorrelative relation between time sensory – motor perception and intelligence in deaf anddumb. There is also a great correlation relation between intelligence and jumping distance inthe deaf and dumb students.